A horizontal linear vibrator for measuring the cross-coupling coefficient of superconducting gravity gradiometers. (April 2021) - Zhang, Lu; Qiu, Yuntao; Liu, Xikai; Chen, Liang; Zhang, Ning; Liu, Xiangdong
Highlights: Parallel leaves suspending structure owns large stiffness in undesired DOFs. Driver design makes the force frictionless, small nonlinear, and controllable. Accompanying motions are elaborately depressed to extremely low levels. The vibrators can work in a cryogenic environment (4.2 K). Abstract: This paper presents a specialized horizontal linear vibrator with small accompanying motions for precisely measuring the cross-coupling coefficient of superconducting gravity gradiometers(SGGs). The vibrator is suspended by leaf springs and actuated by superconducting coils(SCs) and permanent magnets(PMs). Innovative distribution of SCs and PMs can generate frictionless, small nonlinear and controllable driving forces, and it also can provide large force moments to cancel the accompanying angular motions. Besides, the vibrator can be incorporated into the liquid helium Dewar and work at a low temperature. The experimental results show that the accompanying motions related to the amplitude ratio of the accompanying vertical acceleration( a z ) and angular accelerations( αx and αy ) to the actuated horizontal linear acceleration( a x ) at 1 Hz are as small as 1.4 × 10 −4, 4.7 × 10 −4 rad/m and 2.8 × 10 −4 rad/m, respectively. With this vibrator, the measurement resolution for cross-coupling coefficients can be estimated to be 1.8 × 10 −8 rad.